Integration of Artificial Intelligence in Orthodontic Diagnosis and Treatment Planning - N S, Vaishnavi; R, Suma; Roy, Rodoshi; Sphoorthi, K S; Ali Khan, Salman; S, Krithi (Journal of Neonatal Surgery, 2025)
Technology has become a part of our daily lives, where an amalgamation of human intelligence and machine learning has influenced our lives to great heights. The machine simulates human intelligence and enhances its responses with self-adapting algorithms. Artificial Intelligence (AI) is transforming the field of orthodontics by enhanced precision in diagnosis, better treatment planning and hence improved patient care. Additionally, AI has contributed immensely to the growth of virtual treatment planning and remote orthodontic consultations, making specialized individualized care more accessible. As AI continues to expand its integration into orthodontic diagnosis and treatment planning is expected to further refine clinical outcomes and patient related care. This paper explores the evolving role of AI in orthodontics, emphasizing its current applications, benefits, drawbacks and future possibilities.